Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Online Pada Aplikasi Shopee: (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Kristen Tentena) - Balebu, Oktafinalisa; Walenta, Abdi Sakti; Balo , Mikhael Jibrael (Fakultas Ekonomi Universitas KristenTentena, 2024)
This study aims to investigate the factors influencing online purchasing decisions on the Shopee application among students at the Faculty of Economics, Christian University of Tentena. It employs a descriptive qualitative research design with observation and questionnaire techniques. The study was conducted within a two-month period at the university campus, with a targeted population of 45 students who use the Shopee app. The sample consisted of 40 students who had made purchases on Shopee at least three times. Data collection was carried out using questionnaires and documentary study methods. Results from the Likert scale analysis showed that product diversity, pricing strategies, trust in transaction proof, and distribution capabilities significantly affect online purchasing decisions. The most influential factor was price, given the student demographic's limited personal income, highlighting the importance of cost-effective options in influencing buyer behavior. This study contributes to understanding the dynamic factors affecting e-commerce consumer behavior in an academic setting and suggests that trust and cautious online engagement are crucial for safe online shopping experiences.